2007
DOI: 10.1177/0149206307308587
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Team Diversity on Team Outcomes: A Meta-Analytic Review of Team Demography

Abstract: Over the past few decades, a great deal of research has been conducted to examine the complex relationship between team diversity and team outcomes. However, the impact of team diversity on team outcomes and moderating variables potentially affecting this relationship are still not fully answered with mixed findings in the literature. These research issues were, therefore, addressed by quantitatively reviewing extant work and provided estimates of the relationship between team diversity and team outcomes. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
962
3
24

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,160 publications
(1,027 citation statements)
references
References 122 publications
38
962
3
24
Order By: Relevance
“…Knowledge diversity was interpreted in the manner described in Table 1 by Jehn (1999) and Liang et al (2007) since this is similar to the interpretations by Horwitz and Horwitz (2007), Jackson et al (1995), and Pelled (1996) and distinct from value diversity unlike the interpretations by Milliken and Martins (1996) and Harrison et al (1998). There are inconclusive results among previous studies concerning the effects of team diversity on outcomes and team processes (Horwitz and Horwitz, 2007).…”
Section: Transactional and Transformational Leadership Theory Was Intmentioning
confidence: 84%
See 4 more Smart Citations
“…Knowledge diversity was interpreted in the manner described in Table 1 by Jehn (1999) and Liang et al (2007) since this is similar to the interpretations by Horwitz and Horwitz (2007), Jackson et al (1995), and Pelled (1996) and distinct from value diversity unlike the interpretations by Milliken and Martins (1996) and Harrison et al (1998). There are inconclusive results among previous studies concerning the effects of team diversity on outcomes and team processes (Horwitz and Horwitz, 2007).…”
Section: Transactional and Transformational Leadership Theory Was Intmentioning
confidence: 84%
“…Knowledge diversity was interpreted in the manner described in Table 1 by Jehn (1999) and Liang et al (2007) since this is similar to the interpretations by Horwitz and Horwitz (2007), Jackson et al (1995), and Pelled (1996) and distinct from value diversity unlike the interpretations by Milliken and Martins (1996) and Harrison et al (1998). There are inconclusive results among previous studies concerning the effects of team diversity on outcomes and team processes (Horwitz and Horwitz, 2007). Liang et al (2007) found that team diversity increases conflicts and Milliken and Martins (1996) found that it produces formal but less frequent communication among members and that teams that are diverse have lower levels of member satisfaction and higher rates of turnover than homogenous groups.…”
Section: Transactional and Transformational Leadership Theory Was Intmentioning
confidence: 94%
See 3 more Smart Citations